Evaluation of the Effect of Application of the ROWFIT Program of Students from UNWE - Stoyanova, Sevdalina (Research Papers, 2021)
The creation of effective program aimed at improving the structural and functional parameters of students and to the reduction of their unhealthy habits and to the information of a healthy lifestyle. The article presents part of research with the main purpose of assessing the physical fitness of students from UNWE and to determine the degree of influence of new methodology ROWFIT on 8 indicators of physical fitness variable nature of indoor rowing ergometer for two semesters. The subject are some basic indicators of physical fitness a total of 8. Five of them were registered the loading of the indoor rowing ergometer – 500m. On the shoulder girdle (lifting a barbell from a leg) and body weight. Strategic importance for achieving the goal is to increase the adaptive potential of students, which provides high efficiency of their motor activity. The results of the study show that based on interval training with high intensity (HIT) ROWFIT with a series of carefully selected exercises have led to significant positive changes in the physical fitness of the cold. The overall effectiveness of program used shows its appropriateness and adequacy for optimizing the physical condition and motility of students. ROWFIT program is accessible, easy to apply and suitable for individual and organized activities.